2020
DOI: 10.1111/jcmm.15139
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide alleviates non‐alcohol fatty liver disease via regulating Nrf2/AMPK/mTOR signalling pathways

Abstract: Non‐alcohol fatty liver disease (NAFLD) is a common disease which causes serious liver damage. Geniposide (GEN), a kind of iridoid glycoside extracted from Gardenia jasminoides fruit, has many biological effects, such as resistance to cell damage and anti‐neurodegenerative disorder. Lipid accumulation was obvious in tyloxapol‐induced liver and oil acid (OA) with palmitic acid (PA)‐induced HepG2 cells compared with the control groups while GEN improved the increasing conditions. GEN significantly lessened the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 32 publications
0
53
0
Order By: Relevance
“…Geniposide is an active extract from the traditional Chinese medicine "Zhizi". Previous studies have reported that geniposide plays an important role in anti-inflammatory, anti-oxidative stress and antitumor activities [5,32,33]. For instance, geniposide acts as a protective factor in hypoxia/reperfusion-related brain barrier impairment by reducing inflammation, oxidative stress, and apoptosis in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geniposide is an active extract from the traditional Chinese medicine "Zhizi". Previous studies have reported that geniposide plays an important role in anti-inflammatory, anti-oxidative stress and antitumor activities [5,32,33]. For instance, geniposide acts as a protective factor in hypoxia/reperfusion-related brain barrier impairment by reducing inflammation, oxidative stress, and apoptosis in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, geniposide acts as a protective factor in hypoxia/reperfusion-related brain barrier impairment by reducing inflammation, oxidative stress, and apoptosis in vitro [32]. Geniposide protects against lipid accumulation by decreasing oxidative stress and inflammation in non-alcohol fatty liver disease (NAFLD) [33]. The antitumor effect of geniposide has been indicated in several types of human cancers [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research also indicated that geniposide can ameliorate barrier dysfunction via AMPK-mediated inhibition of the MLCK pathway 19 . Previous studies demonstrated that geniposide has bene cial effects on liver diseases both in vivo and vitro 34,35 . The present study concludes that the action mechanism of the CG combination on NAFLD is multi-targeting.…”
Section: Discussionmentioning
confidence: 99%
“…ZZDHD has been extensively used for clearing heat and eliminating dampness and jaundice for many years in China, and it is further thought to have liver-protective, choleretic, and anti-in ammatory effects. A previous study has reported that geniposide could prevent hepatocyte injury [34]. Geniposide is hydrolyzed into genipin under the action of beta-D-glucosidases in intestinal bacteria, which is required for its choleretic action [35].…”
Section: Discussionmentioning
confidence: 99%